2017
DOI: 10.1155/2017/6267036
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Henry and Michael Reactions with Nitroalkanes Promoted by Potassium Carbonate as a Versatile Heterogeneous Catalyst

Abstract: The use of a simple weak inorganic base such as potassium carbonate facilitated the formation of carbon-carbon bonds through both the Henry and the Michael reactions with nitrocompounds. The application of this catalyst under environmentally friendly solventless heterogeneous conditions gave satisfactory to good yields of β-nitroalcohols, involving aliphatic and aromatic starting materials, as well as high to excellent yields in the formation of Michael adducts using several different Michael acceptors and nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…If a primary nitroalkane or nitromethane are selected as reactants, acidic protons will still remain in the nitroalcohol after the addition reaction, making it possible for the water elimination to give rise to nitroalkenes, which correspond to the major secondary product of the Henry reactions under the studied conditions. Thus, a small amount of base and low to moderate temperatures must be used in order to achieve good selectivity for the β-nitroalcohol compounds [60,61]. Typically, an excess of the nitroalkane is added in this equilibrium reaction to ensure the formation of the nitroalcohols in good yields, since they are important building blocks and precursors of a wide variety of other longer-chain compounds, endowed with functional groups essential in chemical synthesis and with biological relevance [62,63].…”
Section: Catalytic Performance In Henry Reactionmentioning
confidence: 99%
“…If a primary nitroalkane or nitromethane are selected as reactants, acidic protons will still remain in the nitroalcohol after the addition reaction, making it possible for the water elimination to give rise to nitroalkenes, which correspond to the major secondary product of the Henry reactions under the studied conditions. Thus, a small amount of base and low to moderate temperatures must be used in order to achieve good selectivity for the β-nitroalcohol compounds [60,61]. Typically, an excess of the nitroalkane is added in this equilibrium reaction to ensure the formation of the nitroalcohols in good yields, since they are important building blocks and precursors of a wide variety of other longer-chain compounds, endowed with functional groups essential in chemical synthesis and with biological relevance [62,63].…”
Section: Catalytic Performance In Henry Reactionmentioning
confidence: 99%
“…Only a small change to the original procedure was necessary for hydro cinnamaldehyde 2d (Table 1, entry 4), which required 15mol% of TMG to provide an 90% yield of the corresponding βnitro alcohol 3d. Regarding reactivity, we found that aliphatic linear aldehydes were more reactive towards this transformation with respect to their branched or aromatic counterparts (Concellón et al, 2006;Bosica and Polidano, 2017). We tested aromatic aldehydes, both benzaldehyde (Table 1, entry 5) and furfural (Table 1, entry 6), but they did not provide sufficient yields after the first transformation due to possible elimination of water and the formation of the corresponding nitroolefins.…”
Section: Strategy and Synthesis Of β-Hydroxy Aminesmentioning
confidence: 99%
“…9−20 Chemical catalysts often need cryogenic conditions, dry solvents, and/or hazardous metals to meet the required stereocontrol synthesis 9,13,17 and are known to associate with side reactions, e.g., retro-Henry and Cannizzaro reaction. 9,21,22 Biocatalysis offers sustainable technology along with high selectivity and efficiency to the synthesis of diverse chemical structural units. Despite numerous advantages, there exist limited biocatalytic transformations for the diastereoselective synthesis of β-nitroalcohols.…”
Section: ■ Introductionmentioning
confidence: 99%